Oblicze agresji zielonogórskich gimnazjalistów = Aggression in Zielona Góra`s middle school students - Wawryk, Lidia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the last few years aggressive behavior has become the subject of studies, observation and analysis by researchers from diverse areas. This phenomenon turned out to be a major problem in Polish schools, most notably in middle ones. This paper presents the results of a study carried out among middle schools students from Zielona Gora. The study focused on the intensity and qualitative characteristics of the aggression syndrome. An attempt is made to identify three kinds of indices: the intensity of respective behavior categories, general aggression syndrome intensity, and aggression direction in teenagers.
Keywords: szkolnictwo ponadpodstawowe; gimnazjaliści; agresja; Zielona Góra